2018
DOI: 10.1002/jbio.201800114
|View full text |Cite
|
Sign up to set email alerts
|

Zinc pthalocyanine‐loaded chitosan/mPEG‐PLA nanoparticles‐mediated photodynamic therapy for the treatment of cutaneous squamous cell carcinoma

Abstract: Zinc pthalocyanine (ZnPc) is a second-generation photodynamic therapy (PDT) sensitizer with sufficient PDT activity for squamous cell carcinoma (SCC). ZnPc is hydrophobic and insoluble in water, which creates hurdles in systemic administration and hence restricts its use in clinic. Here we have loaded ZnPc on chitosan/methoxy polyethylene glycol-polylactic acid (CPP) nanoparticles to form Z-CPP to enhance PDT efficacy. In vitro and in vivo studies were performed to see dark toxicity of the compounds ZnPc, CPP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Loaded ZnPcs on chitosan/methoxy polyethylene glycol-polylactic acid (CPP) was used to form NP-(Z-CPP), and the dark toxicity and efficacy of topical PDT in SCC was examined using in vivo and in vitro tests. The results demonstrated that the compounds exhibited no dark toxicity, and the efficacy of PDT was significantly better using Z-CPP than using free ZnPcs ( 82 ).…”
Section: Application Of Nano-pdt In Skin Cancermentioning
confidence: 99%
“…Loaded ZnPcs on chitosan/methoxy polyethylene glycol-polylactic acid (CPP) was used to form NP-(Z-CPP), and the dark toxicity and efficacy of topical PDT in SCC was examined using in vivo and in vitro tests. The results demonstrated that the compounds exhibited no dark toxicity, and the efficacy of PDT was significantly better using Z-CPP than using free ZnPcs ( 82 ).…”
Section: Application Of Nano-pdt In Skin Cancermentioning
confidence: 99%
“…In addition, Keyal et al [ 57 ] investigated whether ZnPc-loaded chitosan/mPEG-PLA NPs topically applied onto tumor surfaces could increase penetration of PS through the keratinized surface of nodular tumors. In vivo studies performed with cutaneous squamous cell carcinoma tumor-bearing mice demonstrated that ZnPc-loaded nanoparticles possessed superior tumor accumulation and lack of systemic cytotoxicity compared to free ZnPc, indicating that the encapsulation of PS into nanocarriers and their subsequent topical application may be a promising platform for the treatment of skin cancers using PDT.…”
Section: Phthalocyanine-polymeric Nanoparticle Delivery Systems For Cancer Photodynamic Therapymentioning
confidence: 99%
“…In the microemulsion method, a surfactant is solubilized into an organic solvent, and then, a solution containing CS with acetic acid and glutaraldehyde is added to form NPs under mechanic stirring [57,58,59]. The CS/NPs can be applied in several administration routes, such as parenteral [60], oral [61], nasal, ocular [62], topical and transdermal [63], increasing the solubility and permeability of different therapeutic agents, ensuring higher bioavailability and maintenance of these compounds in the body [64].…”
Section: Nanomedicinementioning
confidence: 99%